2013
DOI: 10.1016/j.ejphar.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dopamine and serotonin receptor antagonists on fencamfamine-induced abolition of latent inhibition

Abstract: The purpose of this investigation was to verify the role of dopamine and serotonin receptors in the effect of fencamfamine (FCF) on latent inhibition. FCF is a psychomotor stimulant with an indirect dopaminergic action. Latent inhibition is a model of attention. Latent inhibition is blocked by dopaminergic agents and facilitated by dopamine receptor agonists. FCF has been shown to abolish latent inhibition. The serotonergic system may also participate in the neurochemical mediation of latent inhibition. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…It was also shown that FCF can act as a positive reinforcer and was hypothesized that opioid receptors mediate the reinforcing effects of FCF [25]. Furthermore, changes in the sensitivity of pre- or postsynaptic DA receptors might underlie both tolerance and sensitization to the effects induced by long-term FCF administration [26, 27]. Some authors suggest that chronic FCF treatment is linked to a modification in Na,K-ATPase activity through the cyclic AMP-dependent protein kinase, nitric oxide synthase (NOS) activity, and cyclic GMP levels in the nucleus accumbens (NAc) and striatum (ST) [28].…”
Section: Resultsmentioning
confidence: 99%
“…It was also shown that FCF can act as a positive reinforcer and was hypothesized that opioid receptors mediate the reinforcing effects of FCF [25]. Furthermore, changes in the sensitivity of pre- or postsynaptic DA receptors might underlie both tolerance and sensitization to the effects induced by long-term FCF administration [26, 27]. Some authors suggest that chronic FCF treatment is linked to a modification in Na,K-ATPase activity through the cyclic AMP-dependent protein kinase, nitric oxide synthase (NOS) activity, and cyclic GMP levels in the nucleus accumbens (NAc) and striatum (ST) [28].…”
Section: Resultsmentioning
confidence: 99%
“…Alterations in concentration levels and neurotransmission receptors related to γaminobutyric acid, acetylcholine, dopamine, glutamic acid, serotonin have been reported in ADHD and ASD (table 1) and genetic variations related to these same neurotransmitters have also been reported in ADHD and ASD (table 2). Carson (2011) noticed that genetic research relating to dopamine and serotonin are associated with the search for novelty and reduced latent inhibition (de Aguiar et al, 2013;Swerdlow et al, 2003) or even cognitive flexibility and working memory. However, in addition to dopamine and serotonin, other neurotransmitters may be involved in creativity and neurodevelopmental disorders.…”
Section: B) Concentrations and Receptors In Neurotransmission Systems...mentioning
confidence: 99%
“…Carson (2011) a remarqué que les recherches génétiques relatives à la dopamine et à la sérotonine sont associées à la recherche de la nouveauté et à une inhibition latente réduite (de Aguiar et al, 2013 ;Swerdlow et al, 2003) ou encore à la flexibilité cognitive et à la mémoire de travail. Cependant, outre la dopamine et la sérotonine, d'autres neurotransmetteurs pourraient être impliqués dans la créativité et les troubles neurodéveloppementaux.…”
Section: B) Concentrations Et Récepteurs Dans Les Systèmes De Neurotr...unclassified